INTERVENSI ISOFLAVON KEDELAI TIDAK BERPENGARUH TERHADAP STATUS INFLAMASI DAN IMUNITAS PADA REMAJA DENGAN KEGEMUKAN - Mira Dewi; Ali Khomsan; Dadang Sukandar (Food and Nutrition Society of Indonesia, 2010)
Overweight/obesity is a condition that has been proven to be interrelated with chronic inflammation and compromised immune system due to disregulation of adipocytokine. The aim of the present study was to evaluate the effect of soy isoflavone on the markers of inflammation and immunity of overweight or obese teenagers. Eighteen overweight or obese teenagers, 9 boys and 9 girls each sex were randomized to one of three intervention groups; 0 ml, 150 ml and 300 ml soy milk, equal to 0 g, 25 g and 50 mg isoflavone everyday for 30 days. The data collected were food consumption, plasma isoflavone concentration, plasma IL6 as indicator of inflammation, and lymphocyte and NK cell count as indicator of immunity. The study showed that nutrient intake of samples were still relatively low. The soy milk intervention significantly increased plasma isoflavone concentration, but not significantly had contribution to the plasma IL6 concentration and lymphocyte and NK cell count. Several kind of food consumed by samples had contribution to the plasma isoflavone concentration, and lymphocyte count. Based on the results, it was suggested that soy isoflavone intervention does not affect the inflammation status and immunity of overweight/obese teenagers.